3D modeling of radiation conditions and dose rates for personnel during dismantling of the roof structures of the Shelter object - Pashynov, M.; Pidbereznyy, S.; Paskevych, S. (Вопросы атомной науки и техники, 2020)
The results of three-dimensional modeling of personnel work conditions in radiation-hazardous conditions of the “Shelter” object, carried out using the software complex HVRC VRdose, are presented. Estimations of dosing loads on personnel during the dismantling of a metal farm on the roof of the “Shelter” object are carried out. The obtained simulation data showed good convergence with the data obtained during the development of a working design for dismantling of this construction.